Perfluorocarbon Nanoparticles: Evolution of a Multimodality and Multifunctional Imaging Agent - Patrick M. Winter (Scientifica)
Perfluorocarbon nanoparticles offer a biologically inert, highly stable, and nontoxic platform that can be specifically designed to accomplish a range of molecular imaging and drug delivery functions in vivo. The particle surface can be decorated with targeting ligands to direct the agent to a variety of biomarkers that are associated with diseases such as cancer, cardiovascular disease, obesity, and thrombosis. The surface can also carry a high payload of imaging agents, ranging from paramagnetic metals for MRI, radionuclides for nuclear imaging, iodine for CT, and florescent tags for histology, allowing high sensitivity mapping of cellular receptors that may be expressed at very low levels in the body. In addition to these diagnostic imaging applications, the particles can be engineered to carry highly potent drugs and specifically deposit them into cell populations that display biosignatures of a variety of diseases. The highly flexible and robust nature of this combined molecular imaging and drug delivery vehicle has been exploited in a variety of animal models to demonstrate its potential impact on the care and treatment of patients suffering from some of the most debilitating diseases.